Barriers to reporting postpartum hemorrhage at different levels of healthcare facilities in Nigeria: a qualitative study - Mohammed, Sirajo; Khuan, Lee; Rajen Durai, Ruth Packiavathy; Ismail, Irmi Zarina; Garba, Saleh Ngaski (Belitung Raya Publisher - Belitung Raya Foundation, 2022)
Background: Maternal mortality reduction remains a world health priority. One of the causes of maternal death is bleeding after childbirth. However, little is known regarding barriers to reporting for postpartum hemorrhage care among postnatal women in Nigeria.